(untitled) (Research, Society and Development, 2021)
The practice of exclusive breastfeeding is recommended by health professionals up to six months of age, after which it is advised to add complementary feeding to the mother’s milk. This is because breastfeeding is a simple, physiological and economic measure that contributes to the health and well-being of mother and baby. However, early weaning is still a reality in Brazil and worldwide and a challenge to be tackled in the context of maternal and child health. Therefore, a literature review was carried out on the factors that lead mothers to perform early weaning of children, also highlighting common practices they use in their daily lives to facilitate the withdrawal of exclusive breastfeeding. Thus, it was possible to analyze that the practice of early weaning is linked to social, economic, psychological, family, cultural and biological factors and, therefore, it is still so common in Brazil. In this context, it can be concluded that, even though breastfeeding is extremely important, there are many obstacles that go against the practice and, therefore, it should be further studied, encouraged and naturalized in society.